CO2–CO2 and CO2–Ar continua at millimeter wavelengths. (January 2021) - Odintsova, T.A.; Serov, E.A.; Balashov, A.A.; Koshelev, M.A.; Koroleva, A.O.; Simonova, A.A.; Tretyakov, M.Yu.; Filippov, N.N.; Chistikov, D.N.; Finenko, A.A.; Lokshtanov, S.E.; Petrov, S.V.; et al.
Highlights: Measurements of the broad mm-wave continuum absorption of pure CO 2 and CO 2 -Ar mixtures. Two independent semiclassical trajectory-based calculations of the absorption are compared to measurements. Significant contribution from true bound dimers is revealed. The formula describing both frequency and temperature dependence of the continuum is suggested for atmospheric applications. Abstract: Broadband spectra of the continuum absorption in pure CO 2 gas and its mixture with Ar are studied at room temperature using a resonator spectrometer within 105–240 GHz. The expected pressure and frequency dependence is observed. The obtained data are validated by two independent calculations of the interaction-induced absorption using a semiclassical trajectory-based method. The observed continuum is interpreted in terms of bimolecular absorption, including a significant contribution from true bound dimers. A simplified formula describing both frequency and temperature dependency of the CO 2 –Ar continuum within a frequency range from 60 GHz to 450 GHz at temperatures from 200 K to 400 K is suggested for use in atmospheric studies.